Innovative Application of Cerebral rSO2 Monitoring During Shunt Tap in Pediatric Ventricular Malfunctioning Shunts. Issue 7 (July 2015) - Abramo, Thomas J.; Zhou, Chuan; Estrada, Cristina; Meredith, Mark; Miller, Renee; Pearson, Matthew; Tulipan, Noel; Williams, Abby
Abstract : Objective: This study aimed to determine the reliability and potential application of cerebral regional tissue oxygenation (rSO2 ) monitoring in malfunctioning ventricular shunts during tap. Methods: This is a prospective case series using convenience sample in subjects with confirmed malfunctioning shunt who had left and right cerebral rSO2 monitoring every 5 seconds before, during, and 1 hour after shunt tap. Results: Ninety-four subjects had cerebral rSO2 monitoring. Sixty-three subjects had proximal malfunctions, and 31 subjects had distal shunt malfunctions. The intrasubject's cerebral rSO2 trend and variability at pretap, during, and posttap times were highly correlated. Overall, the average rSO2 is lower in pretap as compared with posttap. Left cerebral rSO2 had lower means and larger SD as compared with right cerebral rSO2 . Left pretap and posttap cerebral rSO2 variability was significantly associated with the location of shunt malfunction regardless of pretap, during, or posttap periods ( P < 0.001), whereas right rSO2 variability was not predictive for malfunction location. Left cerebral rSO2 variability showed utility for identifying the location of malfunction with area under the receiver operating characteristic curve equal to 0.8. Conclusions: Reliable cerebral rSO2 readings before, during, and after shunt tap were demonstrated. Left cerebral rSO2 changes from before to after shunt tap were more predictive for shunt malfunction location than right cerebral rSO2 changes. Observing cerebral rSO2 changes in relationship to shunt tap represents a potential surrogate in measuring cerebral pressures and blood flow changes after cerebral spinal fluid drainage. Significantly greater cerebral rSO2 changes occur for distal malfunction versus proximal malfunction after shunt tap, indicating its potential as an adjunct tool for detecting shunt malfunction type.